Gestión financiera y la rentabilidad del Consorcio Fluvial del Amazonas SRL, Iquitos - periodo 2022 - Ruiz Lopez, Ghierlly Kimberly (2025)
The objective of this research is to evaluate the relationship between financial management and profitability in the Consorcio Fluvial del Amazonas SRL, Iqui tos - period 2022, with a type of quantitative research of non-experimental de sign and a type of cross-sectional design with a correlational approach, includ ing a population of 32 managers and employees of the Consorcio Fluvial del Amazonas SRL, I used the survey technique and a questionnaire as an instru ment, it was concluded that there is a moderate positive correlation of 0.590 between Financial Management and Profitability, and this relationship is sta tistically significant. This indicates that effective financial management is as sociated with higher profitability. Well-implemented financial management practices tend to improve the company's financial results, and the moderate positive correlation (0.588) between Financial Management and Sustainable Growth is also significant. This suggests that sound financial management contributes to the sustainable growth of the company. Companies that manage their finances well tend to experience stronger, more sustainable long-term growth